THE MOTIF OF LOVE IN THE WORKS OF ABDULLAH QADIRI (Conferencea, 2024)
In this article are analyzed, the image of love between Otabek and Kumush, Anvar and Rana, the main characters of the novels of the great writer Abdullah Qadiri, such as “Bygone Days” and “Scorpion from the Altar”, and the drawn artistic style created by the writer.